Removal of Tetracycline from Wastewater by Activated Carbons - Chen, J.; Wang, J.P.; Tao, W.H.; Zhang, G.C. (Asian Journal of Chemistry, 2012)
The adsorption and desorption of tetracycline were investigated by static experiments, with two kinds of activated carbons employed as adsorbents. The related properties of the adsorbate and adsorbents were studied to support the adsorption mechanism exploration. The simulated wastewater was used to test the removal efficiency of tetracycline by activated carbon A. The results suggested that fairly strong H-bonding exists between the functional groups of activated carbons and tetracycline and activated carbon is a promising adsorbent for tetracycline removal in the wastewater. The HCl solution can be used as desorption reagent.